Detecting Periodontal Destruction with Saliva Biomarkers in Aging: Systematic Review - Pitu Wulandari; Syarida Hasnur binti Syafii; Julia Maharani; Olivia Avriyanti Hanafiah; Irma Ervina; Mutia Amalia Nasution (TALENTA, 2025)
Immuno-inflammatory responses to bacteria in dental biofilms can lead to periodontal destruction, which can be indicated by inflammatory markers in saliva. This review highlights salivary biomarkers for detecting periodontal damage as elderly.Two independent reviewers conducted a systematic literature search on PubMed for English publications from 1961 to 2024 using keywords like “aging,” “saliva,” “biomarkers,” and “periodontitis.” The search included only randomized controlled trials that examined salivary biomarkers in aging populations. Out of 160,647 publications, four high-quality studies were included—two from Europe (Switzerland and Slovakia), one from the United States, and one from South Korea. The identified salivary biomarkers included Interleukin-1β, Interleukin-6, matrix metalloproteinases (MMP-3, MMP-8, MMP-9), advanced glycation end products (AGEs), advanced oxidation protein products (AOPP), and total antioxidant capacity (TAC). Based on the published studies, saliva biomarkers are valuable indicators of periodontal disease during aging.